FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU MASYARAKAT DALAM PENGGUNAAN FASILITAS LAYANAN INTERNET PADA MOBIL PUSAT LAYANAN INTERNET KECAMATAN (MPLIK) DISTRIK 13 DI KABUPATEN BOJONEGORO - , SISKA KUSUMA WARDANI; , Dr. Kuskridho Ambardi, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research raised the title of â Factors That Effecting Users Behavior Toward Internet Service in Internet Mobile Subdistrict Internet Center (MPLIK) 13 District of Bojonegoro. The research aims to determine. What factors that affecting users behavior in the use of internet service facility in Mobile Subdistrict Internet Center (MPLIK) 13District of Bojonegoro. This research uses a model approach by adopting the Unified Theory of Acceptance and Use of Technology (UTAUT). The data was collected survey method by distributing questionnaires to the people within three districts which became the location to the operation of Mobile Subdistrict Internet Center (MPLIK) 13District of Bojonegoro. The result of the research prove that factors performance expectancy, social influence and facilitating condition that effecting users behavior toward internet service in Mobile Subdistrict Internet Center (MPLIK) 13District of Bojonegoro. Effort expectancy factors do not contribute to the use of behavior. Significant coefficients of the moderating gender and age on performance expectancy and facilitating condition indicates that this variable is a pure moderating variabel anad can be placed as an independent variable. But in moderating influence of age affects performance expectancy, effort expectancy, social influence toward the use behavior indicates that this age is a moderating variable.